Psychosocial Barriers of Unmet Need Among Woman of Reproductive Age - Ajeng Hayuning Tiyas; Mochammad Anwar; Umu Hani Edi Nawangsih (SEAJOM: The Southeast Asia Journal of Midwifery, 2018)
Women with unmet need are those who are fecund and sexually active but are not using any method of contraception but do not want to conceive either to prohibiting or limiting pregnancy. The unmet need increases the risk of maternal mortality from unwanted pregnancy and unsafe abortion. The percentage of unmet need in Yogyakarta exceeds the national average percentage and Kraton District is the highest region of unmet need in Yogyakarta. Objective: Exploring in-depth information on the barriers of women of reproductive age to use contraception leads to unmet need behavior in terms of psychosocial aspects Method: This research was qualitative research with a phenomenological approach. The informants were taken by purposive sampling technique with criterion sampling strategy. The main informants were 7 women with unmet need and supporting informants as many as 11 people. Data collection techniques used in-depth interview and document study. Data analysis using thematic analysis. Results : Various themes were found to address psychosocial barriers, personal barriers were the main barriers behind women to behave unmet need, including lack of understanding of appropriate contraceptives and unwanted pregnancy risk, weak motivation in using contraception, negative perceptions of contraception, low perceptions of fertility, high self-efficacy against pregnancy prevention strategies and positive coping mechanisms against the risk of pregnancy are undesirable. Conclusion: Personal barriers are the main obstacles for women of reproductive age to behave unmet need. It needs effective counseling optimization, emphasis on impact and risk of unmet need and strengthening of motivation to use modern contraception in order to increase the sustainability of contraception use and prevent drop out and unmet need for contraception.